HANNAH ARENDT LEITORA DE KANT: IMAGINAÇÃO, COMUNICABILIDADE, SENTIDO, LINGUAGEM - JUSTO, José Miranda (Faculdade de Filosofia e Ciências, 2017)
In her The Human Condition Hannah Arendt is particularly critic towards what she considers to be Kant’s «utilitarianism» and «anthropocentrism». Later, however, Arendt will draw on Kant’s Critique of Judgment to construct her political theories and to discuss themes such as imagination, communicability, sense, language and especially metaphor.